Respostas

2014-05-08T14:45:11-03:00
(x - 1).(x - 2) = 6
x² - 2x - x + 2 = 6
x² - 3x + 2 - 6 = 0
x² - 3x - 4 = 0

Δ = (- 3)² - 4 . 1 . (- 4) 
Δ = 9 + 16                                  X = - (- 3) +- √25  / 2 . 1
Δ = 25                                        X = 3 +- 5  / 2
x' = 3 + 5 / 2 => 8 / 2 = 4                    x" = 3 - 5 / 2 => - 2 / 2 = - 1

(x + 1)² = 7 + x
(x + 1) . (x + 1) = 7 + x
x² + x + x + 1 = 7 + x
x² + 2x + 1 - 7 - x = 0
x² + x - 6 = 0

Δ = 1² - 4 . 1 . (- 6)
Δ = 1 + 24                                X = - 1 +- √25  / 2 . 1
Δ = 25                                      X = - 1 +- 5  / 2
x' = - 1 + 5 / 2 => 4 / 2 = 2                      x" = - 1 - 5 / 2 => - 6 / 2 = - 3
1 5 1
ajudou bastante querida obrigado
de nada :)